Burn visits to a pediatric burn center during the COVID-19 pandemic and 'Stay at home' period. Issue 2 (March 2021) - Sethuraman, Usha; Stankovic, Curt; Singer, Adam; Vitale, Lisa; Krouse, Carolyn Backes; Cloutier, Dawn; Donoghue, Lydia; Klein, Justin; Kannikeswaran, Nirupama
Highlights: Emergency Department and trauma visits decreased during COVID-19 pandemic Proportion of burn visits and severity increased during Stay at Home Order period There was a significant increase in proportion of house fire related burns Community reeducation about safety measures to prevent burn injuries is critical